Reducing the Spring Barrier in Predicting Summer Arctic Sea Ice Concentration. Issue 8 (17th April 2023) - Zeng, Jingwen; Yang, Qinghua; Li, Xuewei; Yuan, Xiaojun; Bushuk, Mitchell; Chen, Dake
Abstract: The predictive skill of summer sea ice concentration (SIC) in the Arctic presents a steep decline when initialized before June, which is the so‐called spring predictability barrier for Arctic sea ice. This study explores the potential influence of surface heat flux, cloud and water vapor anomalies on monthly to seasonal predictions of Arctic SIC anomalies. The results show an enhancement in skill predicting Arctic September SIC in the models that use surface fluxes, clouds, or water vapor in combination with SIC and surface sea temperature as predictors when initialized in boreal spring. This result shows the potential to reduce the spring barrier for Arctic SIC predictions by including the surface heat budget. The enhanced predictive skill can be very likely linked to the improved representation of the thermodynamics associated with water vapor and cloudiness anomalies in spring. Plain Language Summary: Under the influence of climate change, the summer sea ice extent in the Arctic presents significant variability and thus is crucial to human activities in the Arctic. However, the predictive skill for summer sea ice in the Arctic shows a steep decline when predictions are initiated before June, which is called the spring barrier. In this study, we show that adding surface heat fluxes (net surface heat flux, net surface long wave radiation and net surface shortwave radiation), clouds or water vapor into a statistical prediction model can better represent the interactive processes at the atmosphere and ocean interface. The enhancement improves the predictive skill of summer sea ice in the Arctic and reduces the spring barrier, especially in areas of the Beaufort Sea, Chukchi Sea, and Central Arctic. Key Points: The predictive skill of summer Arctic sea ice using statistical prediction models presents a steep decline initialized before June The spring barrier can be reduced, but not eliminated, by using spring surface heat fluxes in combination with sea ice concentration and sea surface temperature The statistical models using surface heat fluxes help to improve representation of thermodynamics associated with water vapor and cloudiness